2014
DOI: 10.1245/s10434-014-4144-1
|View full text |Cite
|
Sign up to set email alerts
|

Ratiometric Activatable Cell-Penetrating Peptides Label Pancreatic Cancer, Enabling Fluorescence-Guided Surgery, Which Reduces Metastases and Recurrence in Orthotopic Mouse Models

Abstract: Background The aim of this study was to evaluate the efficacy of using matrix metalloproteinase-2 (MMP-2) and matrix metalloproteinase-9 (MMP-9)-cleavable ratiometric activatable cell-penetrating peptides (RACPPs) conjugated to Cy5 and Cy7 fluorophores to accurately label pancreatic cancer for fluorescence-guided surgery (FGS) in an orthotopic mouse model. Methods Orthotopic mouse models were established using MiaPaCa-2-GFP human pancreatic cancer cells. Two weeks after implantation, tumor-bearing mice were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 26 publications
(29 reference statements)
1
23
0
Order By: Relevance
“…Similar designs have subsequently been published utilizing matrix metalloproteases, caspases or other enzymes [75]. Activatable PTDs/CPPs coupled to fluorescent probes have potential to assist as molecular navigation tools during surgery [76,77]. Furthermore, when combined to classical targeting peptides, such as RGD or GalNac, they can become a very useful addition to enhance specific uptake at precise target sites.…”
Section: Arginine-rich Ptds/cpps and Endosomal Escapementioning
confidence: 99%
“…Similar designs have subsequently been published utilizing matrix metalloproteases, caspases or other enzymes [75]. Activatable PTDs/CPPs coupled to fluorescent probes have potential to assist as molecular navigation tools during surgery [76,77]. Furthermore, when combined to classical targeting peptides, such as RGD or GalNac, they can become a very useful addition to enhance specific uptake at precise target sites.…”
Section: Arginine-rich Ptds/cpps and Endosomal Escapementioning
confidence: 99%
“…Diagnosis of HNSCC is often made at an advanced stage, partly due to the lack of reliable non-invasive methods to accurately identify malignant lesions [2630]. Our lab has established the use of MMP sensitive RACPPs for image-guided surgery of tumors in various animal xenograft and transgenic models of breast cancer [20, 23], pancreatic cancer [21], melanoma and HNSCC [22]. In this study, we have successfully generated oral cavity SCC in an immunocompetent rodent model as previously described [10] and used established MMP responsive ratiometric fluorescence imaging, for comparative detection of cancerous lesions using white light inspection.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported the use of MMP activatable cell penetrating peptides (ACPPs) probes for image guided surgery of tumors in various animal models of breast cancer [20], pancreatic cancer[21], melanoma and head and neck xenografts[22, 23]. We have also demonstrated significant correlation of ratiometric fluorescence (Cy5:Cy7) from the MMP cleavable RACPP with tumor burden in a pancreatic tumor mouse model [21]. Concentration of other MMPs including, MMP 1 and 3 in human saliva and oral cancer are strong diagnostic markers oforal SCCA [8].…”
Section: Introductionmentioning
confidence: 99%
“…Nguyen et al reported significantly improved outcomes when ACPP guidance was compared to bright light surgery in mouse models of human fibrosarcoma and melanoma [48]. Metildi et al demonstrated that MMP-2 and MMP-9-cleavable ratiometric activatable cell-penetrating peptides (RACPPs) conjugated to Cy5 and Cy7 fluorophores could effectively label pancreatic cancer in an orthotopic mouse model, and that FGS using this method reduced metastasis and recurrence [49]. …”
Section: Development Of Tumor Selective Fluorescence Labelingmentioning
confidence: 99%